Perancangan lanskap realitas virtual: transformasi rehabilitasi disabilitas - Gde Bagus Andhika Wicaksana; Made Suryanatha Prabawa; Made Anggita Wahyudi Linggasani; Ida Bagus Gede Parama Putra Putra; Ni Komang Indra Mahayani; Made Mas Surya Wiguna; I Nyoman Darma Kotama; Putu Nugrahaeni Widiasavitri (Prodi Arsitektur Lanskap, Fakultas Pertanian, Universitas Udayana, 2025)
The technology used in everyday life also advances throughout time. Likewise, as time goes on, there will undoubtedly be a rise in the number of persons with disabilities. People with this impairment have personalities that are distinct from those of typical people. Their primary personality trait is that they tend to withdraw from others since they perceive themselves as unique. Because keeping to oneself will adversely impact your psychological and mental wellbeing. Any form of therapy will be unsuccessful if mental and psychological health are compromised. It is entirely feasible to integrate rehabilitation techniques for people with disabilities with modern technology, such as virtual reality (VR). Virtual reality enables the creation of customized virtual settings and landscapes.With the support of a virtual environment, needs can be met quickly. This research uses a participatory approach with descriptive-qualitative trial method because it tests psychological feelings through VR Landscape Design experience. This research found out that treatment for individuals with impairments can be improved since the virtual environment can be displayed as a game application. Future environmental assets for therapeutic game applications have a great deal of promise thanks to research into the design process of virtual landscapes. Based on the results of trials on patients with disabilities, it was concluded that, the comfort of the therapy process is greatly influenced by the visualization of virtual landscapes. Virtual landscapes must appear different from reality, like a dream world, and have features where patients can play and receive encouragement from pre-existing animations in the digital VR environment